Analysis of Intertextuality on Short Stories Entitled Hanya Isyarat by Dewi Lestari and Love by Guy De Maupassant - Miza Rahmatika Aini; Febby Cahyani (Universitas Islam Balitar, 2023)
This study, which was conducted by two researchers, had the objective of analyzing the intertextuality of the short story literary works